New method of increasing the efficiency of signal reception based on high-precision iterative decoding algorithms - Shukhratovich, Atadjanov Sherzod (IFIP International Conference on Wireless and Optical Communications Networks (Print), 2019)
The article discusses an iterative decoding method based on posterior probabilities to improve the energy characteristics of the transmission of information bits. An algorithm for high-precision iterative decoding is developed taking into account the maximum likelihood factor.